Characterization and Enzymatic Assay of Cellulase-Producing Probiotic Bacteria Isolated from Traditional Fermented Bamboo of Bangladesh - Marma, Mauching; Chakroborty, Koushik; Lee, Jong Min; Rahman, Zinia; Rafiquzzaman, S. M. (HAYATI Journal of Biosciences, 2025)
Fermented bamboo (also known as Ngwopo) is a traditional food item among the indigenous population living in the south-east of Bangladesh. Though fermented foods harbour a significant number of probiotics and enzyme-producing bacteria, there is a lack of research on isolating beneficial bacteria from native fermented food products in Bangladesh. Thus, considering the extensive utilisation of cellulase enzymes and probiotics, our study was conducted with the objective of isolating and characterizing native cellulase-producing bacteria from fermented bamboo and performing crude enzyme activity assay. The sample was collected from Khagrachari hill tracts district of Bangladesh. Three isolated bacteria, namely FB-1, FB-2, and FB-3, screened based on the carboxymethyl cellulose medium, were tested for biochemical and probiotic properties, and the best isolate was genetically identified by molecular characterization through 16S rRNA gene sequencing and evolutionary analysis. All three gram-positive isolates were observed to be positive for starch hydrolysis and fermentation of sucrose, suggesting their ability to breakdown carbohydrates while testing negative for gelatinase, indole, and H2S test. The isolates demonstrated moderate bile salt and pH tolerance and low to medium autoaggregation. FB-2 had 75% susceptibility to the tested antibiotics, while other isolates were susceptible to 50% antibiotics. All of the bacteria were non-pathogenic, showing γ-haemolysis. FB-2 strain showed an enzyme production capacity of 1.56 units/ml. The best performing isolate was identified as Bacillus cereus. Therefore, the study discovered a native bacteria potentially suitable as probiotic and as a source of cellulase for industrial processes, highlighting the enriched indigenous cuisines of Bangladesh.